DESIGN AND DEVELOPMENT OF TETOS APPLICATION FOR LOCATION DETECTION IN SUPPORTING DISASTER VICTIM SEARCHING BASED ON GLOBAL POSITIONING SYSTEM (GPS) - Muhammad Lulu Latif Usman; Asep Adang Supriyadi; Aris Poniman; Muhammad Nugraha; Nopi Rahmawati (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
Indonesia is a country with a high level of disasters where during 2005-2015 there were 11,648 hydrometeorological disasters and 3810 geological disasters. In terms of technology, Indonesia is using mobile devices with high growth according to data from the Ministry of Communication and Information. One of the ways to increase the use of mobile devices in assisting disaster management in Indonesia can be developed in the location-based discovery of disaster victims. The location in a mobile device uses a Global Positioning System (GPS) where the existing data is in the form of Latitude and Longitude data. The aim of this research is that the application is expected to assist in the discovery of disaster victims based on the last GPS location. This study focuses on developing a disaster victim search application based on the Android operating system. Development uses the Agile Model by using Black-box Testing and White-Box Testing techniques, where the type of testing uses Unit Testing, Integration Testing, and Acceptance Testing with qualitative data. The results of the research obtained an application in the form of a prototype where there are several corrective inputs obtained from Acceptance Testing. This study is then expected that the application can be applied in disaster management systems in Indonesia which of course can be supported by binding rules so that the data obtained can be utilized optimally.